POTENSI ARANG AKTIF DARI TULANG SAPI SEBAGAI ADSORBEN ION BESI, TEMBAGA, SULFAT DAN SIANIDA DALAM LARUTAN - ', Syamberah; Anita, Sofia; Hanifah, T. Abu (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Chemically the composition of cow bones preparation consist of 69% of inorganic phase, 22% of organic phase and 9% water. The organic phase of bone contains 90% collagen. Therefore, the organic phase of cow bone can be used as a source of carbon that functions as the active charcoal bone. Active charcoal cow bones made of carbonization and activation process, using activator Na2CO3 with variation concentration of 2.5%; 5% and 7.5%. In this study, the active charcoal cow bones with the variation of concentration are characterizated and obtained the optimum concentration of Na2CO3 at concentrations of 5% to 7.99% of moisture content, 13,33% of ash content, 27,164 m2/g of methylene blue adsorption and 184, 6947 mg/g of iod adsorption. The active charcoal cow bones with Na2CO3 5% was utilized to adsorp ions of iron (SNI 6989-4-2009), copper (SNI 6989-6-2009), sulfate (SNI 06-2426-1991) and cyanide (SNI 6989-76-2011) in solution for 24 hours with variations of the concentration of 100, 200, 300, 400, 500 and 600 mg/L. Ions of iron and copper were analyzed using an Atomic Absorption of Spectrofotometer (AAS), while ions of sulphate and cyanide analyzed using a Spectrofotometer UV-VIS. The Optimum adsorption ability of active charcoal cow bones is 99,9624% of the iron ions at a concentration of 300 mg/L, copper ions at 99,6484% that obtained at a concentration of 200 mg/L, sulfate ions at 68,274% and 69,594% of cyanide ions at a concentration of 200 mg/L.